Natural Products Modulate Cell Apoptosis: A Promising Way for the Treatment of Ulcerative Colitis - Liu, Chenhao; Zeng, Yiwei; Wen, Yulong; Huang, Xinggui; Liu, Yi (Frontiers in Pharmacology, 2022)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease impacting patients’ quality of life and imposing heavy societal and economic burdens. Apoptosis of intestinal epithelial cells (IECs) has been considered an early event during the onset of UC and plays a crucial role in disease development. Thus, effectively inhibiting apoptosis of IECs is of critical significance for the clinical management of UC, presenting a potential direction for the research and development of pharmacotherapeutic agents. In recent years, research on the ameliorative effects of natural products on UC through inhibiting IECs apoptosis has attracted increasing attention and made remarkable achievements in ameliorating UC. In this review, we summarized the currently available research about the anti-apoptotic effects of natural products on UC and its mechanisms involving the death-receptor mediated pathway, mitochondrial-dependent pathway, ERS-mediated pathway, MAPK-mediated pathway, NF-κB mediated pathway, P13k/Akt pathway, JAK/STAT3 pathway, and NLRP3/ASC/Caspase-1 pathway. Hopefully, this review may yield useful information about the anti-apoptotic effects of natural products on UC and their potential molecular mechanisms and provide helpful insights for further investigations.